Francois Simiand's Theory of Economic Progress - Marjolin, Robert; Jaffe, G.; Jaffe, W. (Review of Economic Studies, 1938)
François Simiand's Theory of Economic Progress Robert Marjolin Robert Marjolin Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 3, June 1938, Pages 159–171, https://doi.org/10.2307/2967444 Published: 01 June 1938